The Influence Of Organizational Culture And Individual Characteristics On The Performance Of Fisherman Group Recipients Of The Coastal Community Economic Empowerment Program (Pemp) In Kendari City - Ilham Wahid; Indrianty Sudirman; Andi Nur Baumassepe (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to 1) determine the types of organizational culture characteristics and individual characteristics of fishermen groups receiving PEMP programs in Kendari City, 2) determine the extent to which organizational culture and individual characteristics influence the performance of fisherman groups, and 3) obtain an overview of the performance of fisherman groups in fund development rolling. The analytical method used in this research is descriptive analysis method and multiple linear regression analysis. The research results show the following findings. 1) Although many factors influence the performance of fishing groups, organizational culture such as individualism, power distance, uncertainty avoidance and masculinity as well as individual characteristics such as age, gender, marital status, education, number of dependents and average income cannot be ignored. fishermen group performance. 2) Based on the results of the analysis using multiple linear regression, the coefficient of determination (R2) is 0.81, which means that 81% of fishermen's performance is influenced by the variables age, gender, marital status, education, number of dependents, average income, individualism, power distance, uncertainty avoidance and masculinity; while the remaining 19% is influenced by other variables that also determine but are not included in the model. 3) The intercept value (constant) based on the results of the analysis is -15.70 which indicates that the performance of the fishermen group in developing the PEMP revolving fund program is below 0 (zero), this means that the work performance of the fisherman group within a certain period of time has not yet returned to the PEMP revolving fund. Keywords: Organizational Culture, Individual Characteristics, and Performance.